COMPARATIVE ANALYSIS OF THE LEVEL OF DIGITAL COMPETENCES OF FUTURE TEACHERS IN POLAND AND UKRAINE - Ewelina Rzońca (Інформаційні технології і засоби навчання)
Digital transformation requires continuous development from the individual, including the development of media competences. Effective education of the young generation requires teachers to have digital competences. On the other hand, teachers are prepared to work in the era of new technologies at universities, where students gain important knowledge and skills. Therefore, the author focused on the digital/media competences of pedagogy students. According to the Digital Competence of Educators [1], these include information and data skills, communication and collaboration, digital content creation, safety, and problem-solving. The article presents the results of its own research, which showed the level of media competence of pedagogy students in Poland and Ukraine and possible differences in this area noticeable in future teachers from the two European countries. 84 students from Ukraine and 102 from Poland participated took part in the survey. The questionnaire was developed on the basis of relevant sources and tools for examining the level of digital competence of teachers: Digital Competence of Educators [1], Simons, Meeus, Sas [2], Selfie for Teachers [3]. The questionnaire covered three areas: media use, media understanding and use, and media creation and transmission. A Likert scale from 1 to 5 was used. In the analysis of the collected data, the following tests were used: Kolmogorov-Smirnov, Mann-Whitney U. Statistical analysis of the obtained data allowed to confirm the hypothesis regarding the lack of statistically significant differences in the level of digital competences of future teachers. The results of the research indicated certain tendencies - a slightly higher level of media competence of students from Ukraine in terms of, m.in knowledge, knowledge of online communication tools with students, netiquette of the use of tools to communicate with colleagues. Therefore, future teachers from both countries are prepared for rational and selective use of media in their didactic and educational work. It is important to constantly supplement the study programs with content corresponding to technological, economic and socio-cultural development.